Strategic maneuvering in argumentative discourse : extending the pragma-dialectical theory of argumentation - Eemeren, F. H. van (Frans Hendrik), 1946- (Argumentation in context ;, 2010)
In Strategic Maneuvering in Argumentative Discourse, Frans H. van Eemeren brings together the dialectical and the rhetorical dimensions of argumentation by introducing the concept of strategic maneuvering. Strategic maneuvering refers to the arguer's continual efforts to reconcile aiming for effectiveness with being reasonable. It takes place in all stages of argumentative discourse and manifests itself simultaneously in the choices that are made from the topical potential available at a particular stage, in adaptation to audience demand, and in the use of specific presentational devices. Stra.